A Comparative Study on Customer Relationship Management Practices in the Telecom Industry - Krishna Mohan Naidu, Y.; S. B., Ponduri (Indian Journal of Marketing, 2015)
A well-functioning telecommunication network is an essential component of the economic infrastructure, it is one of the prime support services needed for rapid growth of any developing country. The state-owned telecom player Bharat Sanchar Nigam Limited (BSNL) needs to wake up to the reality and realize the importance of satisfying and retaining the customers. The service providers design and deploy customer centric strategies not only to grab a huge amount of the market share, but also to sustain themselves in the long-term. Banks have relationship managers, airlines have frequent flyer programs, credit cards offer redeemable bonus points for increased card usage, hotels have personalized services, and telecom service operators provide customized services to their users. Relationship marketing is emerging as the core marketing activity for businesses operating in fiercely competitive environments. On an average, every business spends nine times more to acquire customers than it does to keep an existing customer with itself. Firms are now paying more attention to their relationships with customers to retain them and to increase their share of customers' purchases. Although customized as well as off-the-shelf technological solutions are available in the marketplace, businesses need to do a lot more than just adopt these solutions to implement customer relationship management (CRM) practices with the aim of reducing the gap between the company and its customers. Today, the Indian telecom industry suffers from major problems of customer attrition in the name of "number portability" because of multiple service providers or close substitutes with zero or less switching costs. Hence, it is inevitable for the companies to develop a CRM strategy that enables them to improve their customer database and also improves the number of loyal customers. In the light of this context, the present research attempted to study CRM practices followed by the major public and private sector telecom service providers in India, that is, BSNL and Airtel.